Effectiveness of additional antireflux surgery after resection of oesophagogastric junction cancer: protocol for a systematic review and meta-analysis - Yang Yu; Hao Chen; Yu Li; Lei Gao; Na Wang; Peng Zheng; Fanghui Ding; Bofang Wang (BMJ Open)
Introduction Gastro-oesophageal reflux is common in patients with oesophagogastric junction (OGJ) cancer following radical surgery. We aim to conduct a systematic review to investigate the effectiveness and clinical value of additional antireflux surgery (pyloroplasty and fundoplication) for OGJ cancer.Methods and analysis We intend to search Medline, Cochrane Library and Embase databases for studies published in English, from database inception to October 2022. Randomised controlled trials and (non-random) controlled clinical trials will be eligible for inclusion. We will search for all eligible studies that have compared proximal gastrectomy plus additional antireflux surgery and proximal gastrectomy alone in patients with resectable OGJ cancer. All potential outcomes related to gastro-oesophageal reflux, including occurrence of reflux symptoms, reflux oesophagitis, reflux occurrence based on barium meal examination, pH of fluid from the lower oesophagus, and 24-hour oesophageal pH test will be assessed as the primary outcomes. Other outcomes, such as patients’ survival and postoperative complications (eg, stenosis, infection and leak) will also be analysed. Two reviewers will independently screen the literature, extract data and assess the risk of bias in the included studies; subsequently, a meta-analysis will be performed using RevMan V.5.3 software to pool the results. The χ2 and I2 tests will be used for heterogeneity assessment and sources of heterogeneity will be explored using subgroup analysis. The Grading of Recommendations, Assessment, Development and Evaluation method will be applied to assess the level of evidence.Ethics and dissemination This proposed study is a secondary analysis of previously published data. Therefore, ethics approval is not required. The results will be presented for publication in a peer-reviewed journal and data will be stored in public databases.